Determinants of Real Earnings Management: A Case of an Emerging Economy - Naz, Farah; Khan, Misbah; Hassan, Abul; Salman, Veera (Organizations and Markets in Emerging Economies, 2026)
This study aims to determine the firm-specific factors that prompt earnings management within Pakistani manufacturing firms from 2013 to 2020. The proxy measure provided by Roychowdhury (2006a) is used to determine the firm’s value of managing earnings upward or downward using real techniques of earnings management. The results show that the leverage, return on assets, audit quality, dividend payout ratio, market competition, and size significantly drive earnings management. In contrast, the tax and market value of equity did not show signs of influencing this practice. The study also found that both downward and upward earnings management were driven by the same incentives, with an overall trend toward a contradictory relationship. Further, the abnormality denoting downward EM and the abnormality denoting upward EM have been segregated to make the research more conclusive on the trends and determinants of EM. It is suggested that in the future studies covering different sectors or stock markets should be conducted. Additionally, forecasting of EM using big data analysis and machine learning can be explored.
Keywords: real earnings management; earnings management; upward and downward earnings management; firm-specific determinants; the Roychowdhury model